Pengaruh kesadaran merek, citra merek, dan kepercayaan konsumen pada minat membeli ulang - Hans Ferdiwan; Kezia Kurniawati Nursalin (Vikara: Student Academic Journal of Business and Management, 2025)
The low-cost carrier (LCC) sector has been increasingly developing in Indonesia, with Citilink as one of the prominent airlines. This study aims to assess the influence of brand awareness, brand image, and consumer trust on repurchase intention using a quantitative approach and multiple linear regression analysis. The sampling technique employed was purposive sampling with a total of 156 respondents. The results indicate that simultaneously, brand awareness, brand image, and consumer trust have a significant effect on repurchase intention. Similarly, not only brand awareness and brand image have an influence, but consumer trust also has an effect on repurchase intention. These findings imply that in enhancing repurchase intention in the airline industry, brand awareness and brand image, along with consumer trust, play a crucial role.